Pengaruh minyak cengkeh dan jenis kemasan terhadap mutu benih dua kultivar kacang hijau (Vigna radiata (L.) R. Wilczek) setelah periode simpan - Sumadi Sumadi; Anne Nuraini; Erni Suminar; Siti Sarah Rubaekah; Muhamad Alvianto (Kultivasi, 2018)
Abstract. Seed storage is one of the efforts to maintain seed quality until the seed is ready to be planted. Some factors that influence seed quality after the storage period are seed storage pest attack, packaging type and seed charac-teristics of each cultivar. The objectives of the experiment was to determine the combination of dosage of clove oil, packaging type and mung bean cultivar. This research consisted of two series of experiments: to study the effectiveness of a combination of clove oil dosage with cultivars and tested combinations of packaging types with two mung bean cultivars. The first experiment was conducted in January - April and the second in April - June 2017 respectively. The first experiment was to obtain the effect of a combination of clove oil dosages (0,0 ml kg-1, 0,5 ml kg-1, 1,0 ml kg-1, 1,5 ml kg-1 and 2,0 ml kg-1) with two mungbean cultivars (Vima-1 and Vima-2). Furthermore, the second experiment was to examine the types of packaging (jute bag, aluminum foil, paper bag, plastic bag and glass bottle) with cultivar type (Vima-1 and Vima-2) .The quality of the seeds was tested three and six months storage respectively. The first experi-mental results showed that clove oil treatment had no significant effect on the population of Callosobrochus sp after three months storage, percentage of broken seeds, weight of 100 grains and germination capacity. In general, Vima-3 cultivars that combined with dosages of clove oil  gave better quality than  of Vima-1 cultivars. The second experimental results showed that the paper bag packaging type and the jute bag are not able to maintain the seed viability and vigor more than  ≥ 80% of the standard quality. Aluminum foil, plastic seals, and glass bottles are able to maintained the seed quality of both cultivars after a six-month storage period.Keywords: clove oil, types of packaging, Mung bean cultivars, storage Sari. Penyimpanan benih merupakan salah satu upaya menjaga mutu benih sampai benih siap ditanam. Faktor-faktor yang mempengaruhi mutu benih setelah periode simpan, antara lain serangan hama gudang, jenis kemasan dan karakteristik benih tiap kultivar. Tujuan penelitian adalah menentukan kombinasi dosis minyak cengkeh, jenis kemasan yang  paling baik  mempertahankan kualitas benih  kacang hijau.Penelitian  terdiri dari dua seri percobaan, yaitu mengkaji keefektifan kombinasi dosis minyak cengkeh dengan dua kultivar kacang hijau serta mengkaji kombinasi jenis kemasan dengan kultivar kacang hijau. Masing-masing dilaksanakan pada bulan Januari – April serta April – Juni 2017. Percobaan pertama mengkaji pengaruh kombinasi antara dosis minyak cengkeh ( 0,0 ml kg-1, 0,5 ml kg-1, 1,0 ml k-1, 1,5 ml kg-1 dan 2,0 ml kg-1) dengan kultivar ( Vima-1 dan Vima-2). Selanjutnya percobaan ke dua adalah untuk mengkaji  jenis kemasan (kantong terigu, aluminium foil, kantong kertas, kantong plastik dan botol kaca) dengan jenis kultivar (Vima-1 dan Vima-2). Mutu benih  diuji setelah periode simpan masing-masing tiga bulan dan enam bulan. Hasil percobaan pertama menun-jukkan bahwa pemberian minyak cengkeh tidak berpengaruh nyata terhadap populasi Calloso-brochus sp pada penyimpanan benih tiga bulan berkisar antara 10,00 – 25,67 ekor, persentase benih rusak, bobot 100 butir dan daya berkecambah. Secara umum kultivar Vima-2 yang dikombinasikan dengan dosis minyak cengkeh mutunya lebih baik diban-dingkan benih kultivar Vima-1.Hasil percobaan kedua menununjukkan bahwa jenis kemasan amplop kertas dan karung terigu tidak mampu mempertahankan daya berkecambah dan vigor  kedua kultivar ≥ 80 % dari standar. Kemasan aluminum foil, kantong plastik dan botol kaca mampu mempertahankan mutu benih kedua kultivar setelah periode simpan enam bulan.Kata kunci : Minyak cengkeh, jenis kemasan, kultivar kacang hijau, penyimpanan